Photoexcitation of graphene with twisted light - Farias, María Belén (2013)
We study theoretically the interaction of twisted light with graphene. The light-matter interaction matrix elements between the tight-binding states of electrons in graphene are determined near the Dirac points. We examine the dynamics of the photoexcitation process by posing the equations of motion of the density matrix and working up to second order in the field. The time evolution of the angular momentum of the photoexcited electrons and their associated photocurrents are examined in order to elucidate the mechanisms of angular momentum transfer. We find that the transfer of spin and orbital angular momentum from light to the electrons is more akin here to the case of intraband than of interband transitions in semiconductors, due to the fact that the two relevant energy bands of graphene originate from the same atomic orbitals.